IDENTIFIKASI FAKTOR PENGHAMBAT KEBERHASILAN REKLAMASI LAHAN BEKAS TAMBANG: STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN MANGAN DI TIMOR BARAT - Binus, Martinus; Mudita, I Wayan; Wulakada, Hamza H. (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
Reclamation of ex-mining land is an obligation that must be carried out by every mining business actors, in order to organize, restore, and improve the quality of the environment and ecosystem so that it can function again according to its designation. However, this obligation has not been carried out consistently by manganese mining companies in West Timor. Based on the results of supervision carried out by mining inspectors, no company has carried out reclamation. This study aims to identify factors that influence the implementation of reclamation governance for ex-mining manganese land in West Timor. Case studies were conducted on eigth location of Izin Usaha Pertambangan (IUP) in West Timor, East Nusa Tenggara Province. Data collection was carried out through questionnaires, interviews, and field observations. Furthermore, data analysis used qualitative descriptive methods. The results of the study indicate that the inhibiting factors for achieving successful reclamation of ex-mining land in West Timor are the licensing process, supervision, competence of mining business actors, and community involvement. In this regard, further research is needed to examine the form of reclamation that is in accordance with the conditions of ex-mining manganese land in West Timor.